Study of the Interaction of Antimicrobial Peptides, in Particular Gramicidin S With Cell Membranes - Perepelitsa, Igor; Berest, Volodymyr; Bozhok, Galyna (Problems of Cryobiology and Cryomedicine, 2024)
Probl Cryobiol Cryomed 2024; 34(4):298